Nghiên cứu thiết kế chế tạo máy đùn viên nén nhiên liệu rdf từ phụ phế phẩm nông nghiệp - Phạm Vũ Nguyên Tịnh (2024)
Nghiên cứu thiết kế chế tạo máy đùn viên nén nhiên liệu rdf từ phụ phế phẩm nông nghiệp